2018
DOI: 10.1038/s41418-018-0113-8
|View full text |Cite
|
Sign up to set email alerts
|

MICU3 is a tissue-specific enhancer of mitochondrial calcium uptake

Abstract: The versatility and universality of Ca2+ as intracellular messenger is guaranteed by the compartmentalization of changes in [Ca2+]. In this context, mitochondrial Ca2+ plays a central role, by regulating both specific organelle functions and global cellular events. This versatility is also guaranteed by a cell type-specific Ca2+ signaling toolkit controlling specific cellular functions. Accordingly, mitochondrial Ca2+ uptake is mediated by a multimolecular structure, the MCU complex, which differs among variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
208
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(227 citation statements)
references
References 74 publications
11
208
2
6
Order By: Relevance
“…Recently, two articles reported that MICU1 can directly interact with the conserved D-ring of MCU to regulate the Ca 2+ uptake [24,25]. MICU1-MICU2 complex has been shown to exert regulatory function for MCU's activity [7,17,23,[26][27][28][29], although how MICU1 interacts with MICU2 to regulate Ca 2+ uptake is not clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two articles reported that MICU1 can directly interact with the conserved D-ring of MCU to regulate the Ca 2+ uptake [24,25]. MICU1-MICU2 complex has been shown to exert regulatory function for MCU's activity [7,17,23,[26][27][28][29], although how MICU1 interacts with MICU2 to regulate Ca 2+ uptake is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been suggested that disulfide formation between MICU2 and MICU1 which is facilitated by oxidoreductase Mia40 stabilizes the heterodimer in physiological condition [23]. Distinct from MICU1, only MICU1-MICU2 heterodimer but not MICU2 alone was detected in cells [18,23,26,28].…”
Section: Introductionmentioning
confidence: 99%
“…MICU1 is broadly expressed in most of the tissues; MICU2 is expressed primarily in visceral organs, whereas MICU3 is mostly in skeletal muscles and the CNS (Pagliarini et al, 2008;Plovanich et al, 2013 (Payne, Hoff, Roskowski, & Foskett, 2017). MICU3 also has the targeting sequence to support its mitochondrial localization, and has been shown to localize in mitochondria (Patron et al, 2019;Plovanich et al, 2013), although it does not achieve the score needed to be listed in MitoCarta (Patron et al, 2019;Plovanich et al, 2013). MICU2 has a conserved domain architecture like MICU1, and is found to reside within mitochondria with high-content microscopy and MitoCarta (an inventory of human and mouse genes encoding proteins with strong support of mitochondrial localization).…”
Section: Micu Family Proteinsmentioning
confidence: 99%
“…However, once cytoplasmic Ca 2+ ([Ca 2+ ] c ) is rapidly elevated (>300-500 nM), the MCU will be activated promptly and transport Ca 2+ into mitochondria, even against the Ca 2+ concentration gradient (Chaudhuri et al, 2013;Kamer, Grabarek, & Mootha, 2017;Marchi & Pinton, 2014). With two TMDs, N-and C-terminals of MCUR1 face the mitochondria inner membrane space Mitochondrion manipulate its activities (Lambert, Luongo, Shah, & Elrod, 2016;Patron, Granatiero, Espino, Rizzuto, & De Stefani, 2019;Perocchi et al, 2010;Plovanich et al, 2013;Sancak et al, 2013). The MCU and its regulatory molecules, including the MCU-dominant negative beta subunit (MCUb), essential MCU regulator (EMRE), MCU regulator 1 (MCUR1), mitochondrial calcium uptake (MICU) 1, MICU2, and MICU3, form a large complex to FIGURE 1 Uniplex components and uniplexmediated mitochondrial Ca 2+ uptake in the global Ca 2+ dynamic.…”
mentioning
confidence: 99%
See 1 more Smart Citation